Exploring the Sociocultural Dynamics of AI in Arabic Language Education in Islamic Schools: Teachers’ Perspectives on Readiness and Challenges - Mubarok Fatahillah (Sahabat Publikasi, 2026)
This study explores the integration of artificial intelligence (AI) into Arabic language education at Islamic higher education institutions, with a particular focus on the sociocultural dynamics, lecturer readiness, and challenges at Sties Khas Al Jaelani. Using a qualitative research design, the study conducted semi-structured interviews with 15 Arabic language lecturers to examine their perceptions of AI adoption, the cultural challenges encountered, and the opportunities AI presents for enhancing language learning. The findings reveal that although AI tools are viewed as potentially beneficial for personalized learning and improving student engagement, lecturers face significant barriers related to insufficient training, inadequate technological infrastructure, and concerns over AI's compatibility with traditional teaching methods and Islamic educational values. Sociocultural factors, particularly fears that AI may undermine the teacher-student relationship and the moral and ethical dimensions of Islamic education, were also found to influence AI adoption. Despite these challenges, lecturers recognized AI's potential to enhance Arabic language learning through personalized feedback and data-driven insights. This study highlights the importance of addressing both technical and cultural barriers to AI integration in Arabic language education within Islamic institutions and suggests that professional development programs and culturally sensitive AI tools are crucial for successful implementation.